Answer:
2. f(x) = 2x - 1, f(0) = -1, f(1) = 1, f(2) = 3
3. f(x) = -3x, f(0) = 0, f(1) = -3, f(2) = -6
4. f(x) = -6x + 4, f(0) = 4, f(1) = -2, f(2) = -8
5. f(x) = 1 - 3x, f(0) = 1, f(1) = 1, f(2) = -5,
Step-by-step explanation:
2. f(x) = 2x -1
f(0) = 2(0) - 1 = -1
f(1) = 2(1) - 1
= 2 - 1
= 1
f(2) = 2(2) - 1
= 4 - + 41
= 3
3. f(x) = -3x
f(0) = -3(0) = 0
f(1) = -3(1)
= - 3
f(2) = -3(2)
= -6
4. f(x) = -6x + 4
f(0) = -6(0) + 4
= 4
f(1) = -6(1) + 4
= -6 + 4
= - 2
f(2) = -6(2) + 4
= -12 + 4
= -8
5. f(x) = 1 - 3x
f(0) = 1 - 3(0)
= 1
f(1) = 1 - 3(1)
= 1 -3
= -2
f(2) = 1 - 3(2)
= 1 - 6
= -5